Challenges of Diagnosis and Treatment of ANCA Associated Vasculitis in COVID-19 Pandemic - A Case Report - Sharma, Prayush; Sijapati, Milesh Jung; Gautam, Santosh; Kandel, Ramesh; Simkhada, Suman; Regmi, Sneha Bandhu (Nepalese Respiratory Journal, 2022)
As COVID-19 pandemic is spreading worldwide with high infectivity rates of various strains, it is also challenging our healthcare system with its respiratory complications, and limited availability of healthcare providers. On the other hand, a huge vaccination program against COVID-19 is being conducted throughout the world. This viral infection and vaccination program has also brought into account the controversies of some neurological and autoimmune complications. Although the exact mechanism of these complications is still unknown, some autoimmune mechanisms have been predicted. These complications may further challenge the management of this novel viral infection. One of the rare complications of COVID-19 infection and its vaccination is de novo development or flare of ANCA-associated vasculitis, which has also been found in many recent case reports.